Manipulation of Front-Surface Profile of Scleral Contact Lenses to Alter Peripheral Refraction. Issue 9 (September 2020) - Peguda, Rajini; Kang, Pauline; Swarbrick, Helen A.
Abstract : SIGNIFICANCE: The front optic zone diameter of scleral contact lenses was manipulated to mimic the central treatment zone induced by orthokeratology contact lens wear, to explore potential effects on the peripheral refraction profile. PURPOSE: The purpose of this study was to investigate effects on the peripheral refraction profile of changing front optic zone diameters of scleral contact lenses. METHODS: Twelve young adults were fitted with scleral contact lenses (diameter, 16.5 mm) with two front optic zone diameters (6 and 4 mm) on one eye only on 2 separate days. Both lenses were fabricated with front optic zone power of −3.00 D and plano power outside the optic zone to mimic the orthokeratology treatment effect. All lenses had the same spherical back-surface design with a toric lens periphery. Peripheral refraction was measured at 10° increments along horizontal (±35°) and vertical (±30°) meridians before lens insertion and after 10 minutes of lens wear. Mixed-model analysis and post hoc t tests with Bonferroni correction were performed. RESULTS: Compared with baseline, no significant change in relative spherical equivalent refraction M was observed with 6-mm optic zone lenses along the horizontal meridian. However, a significant difference in relative M profile was found with 4-mm optic zone lenses ( P = .009). M became myopic at all locations in the nasal visual field ( P < .05) except at 35°. In contrast, compared with baseline, no significant changes in relative M were found with either 6- or 4-mm optic zone lenses along the vertical meridian. CONCLUSIONS: The greater myopic shift in relative peripheral refraction with 4-mm compared with 6-mm front optic zone lenses suggests that a reduced treatment zone diameter in orthokeratology may induce more myopic peripheral refraction changes. This may guide us toward novel orthokeratology lens designs for more effective myopia control.